La gran dama: Science Patronage, the Rockefeller Foundation and the Mexican Social Sciences in the 1940s - Álvaro Morcillo Laiz (Journal of Latin American Studies, 2019)
If Latin America's public universities are considered part of the state, then it seems plausible to characterise them as similar to the state, i.e. as clientelistic. However, this plausible hypothesis has never been examined by the literature on twentieth-century Mexican social sciences. Just like clientelism, science patrons such as US philanthropic foundations have similarly been neglected. In this article I argue that, as an alternative to what the Rockefeller Foundation perceived as clientelism and amateurism at Latin American universities, it claimed to patronise liberal scholarship, practised according to formal rational criteria. While foundations have been frequently considered part of a US imperialistic drive towards cultural hegemony in Latin America, they were not unitary actors and frequently failed to predict the actual impact of their grants. In Mexico in the 1940s, the Rockefeller Foundation boosted the humanities, but missed the opportunity to support a local take on social science teaching and research. – – Si las universidades públicas latinoamericanas son consideradas parte del Estado, resulta lógico caracterizarlas como similares al Estado, es decir, como clientelistas. Sin embargo, esta plausible hipótesis nunca ha sido examinada por la literatura sobre las ciencias sociales mexicanas en el siglo XX. Tampoco han sido bien estudiados otros patrocinadores de la ciencia como las fundaciones filantrópicas norteamericanas. En este artículo argumento que, como una alternativa a lo que la Fundación Rockefeller percibió como clientelismo y amateurismo en las universidades latinoamericanas, esta pretendió patrocinar una investigación liberal, practicada de acuerdo a un criterio racional formal. Mientras que las fundaciones han sido con frecuencia consideradas como parte de una ambición imperialista de ejercer una hegemonía cultural en Latinoamérica, estas no fueron actores unitarios y con frecuencia fracasaron en predecir el impacto real de sus subvenciones. En México de los 1940s, la Fundación Rockefeller reforzó las humanidades, pero perdió la oportunidad de apoyar una visión local de la ense\~nanza e investigación en ciencias sociales.
Keywords: 330; intellectual history; history of sociology; clientelism; cultural diplomacy; US–Latin American relations; Mexico; historia intelectual; historia de la sociología; clientelismo; diplomacia cultural; relaciones EEUU–Latinoamérica; México